Geophysical studies of the internal structure of glacial-permafrost stone formations of the Central Altai - G. Dyakova S.; A. Goreyavcheva A.; O. Ostanin V.; V. Olenchenko V.; R. Biryukov Yu.; Г. Дьякова С.; А. Гореявчева А.; О. Останин В.; В. Оленченко В.; Р. Бирюков Ю. (Ice and Snow, 2020)
Several complexes of glacial-permafrost stone formations have been studied in the Central Altai using geophysical methods. The features of their internal structure together with characteristic differences between them depending on the dynamic activity, altitude and geomorphological characteristics were determined. Integration of the methods of the electrical resistivity tomography and the GPR-sounding made it possible to distinguish roofs on all the studied formations and to estimate thicknesses of the stone-ice cores. Studying of eight formations with different degrees of activity and located at different altitudes did show that the thicknesses of the stone-ice cores increase with height: from 8–10 m in the mid-mountain zone up to 18-20 m in the highlands. The values of the specific resistance of cores inside the glacial-stone formations are directly proportional to altitudes of the objects (the correlation coefficient is 0.7) that give an indication of increasing in the amount of ice in them with height. The depth of occurrence of the roof of the stone-ice material in the formations is more dependent on the exposure of the slope on which the object is located, and changes from 1–2 m on slopes of the Northern exposure up to 4–6 m on slopes of the Southern and Western exposures. C помощью комплекса методов электротомографии и георадиолокационного зондирования установлена глубина залегания и оценена мощность каменно‑ледяных ядер, а также прослежена взаимосвязь морфологии поверхности и внутреннего строения гляциально‑мерзлотных каменных образований Центрального Алтая.